Scalable Thousand Channel Penetrating Microneedle Arrays on Flex for Multimodal and Large Area Coverage BrainMachine Interfaces (Adv. Funct. Mater. 25/2022). (17th June 2022) - Lee, Sang Heon; Thunemann, Martin; Lee, Keundong; Cleary, Daniel R.; Tonsfeldt, Karen J.; Oh, Hongseok; Azzazy, Farid; Tchoe, Youngbin; Bourhis, Andrew M.; Hossain, Lorraine; Ro, Yun Goo; Tanaka, Atsunori; et al.
Abstract : Microneedle Arrays In article number 2112045, Shadi A. Dayeh and co‐workers have invented an advanced brain–computer interface with a flexible and moldable backing and penetrating microneedles, which are 10 times thinner than the human hair. The flexible backing allows the device to more evenly conform to the brain's complex curved surface and to more uniformly distribute the microneedles that pierce the cortex without piercing surface venules and to record signals from nearby nerve cells evenly across a wide area of the cortex.